If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 = g + -15 Reorder the terms: 12 = -15 + g Solving 12 = -15 + g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-1g' to each side of the equation. 12 + -1g = -15 + g + -1g Combine like terms: g + -1g = 0 12 + -1g = -15 + 0 12 + -1g = -15 Add '-12' to each side of the equation. 12 + -12 + -1g = -15 + -12 Combine like terms: 12 + -12 = 0 0 + -1g = -15 + -12 -1g = -15 + -12 Combine like terms: -15 + -12 = -27 -1g = -27 Divide each side by '-1'. g = 27 Simplifying g = 27
| 75=-12 | | (-3-x)(-x+3)= | | 0.2(0.5x-4)7.4=-96 | | x+1/2x-3/2x=1/6 | | v-9=-5 | | 2k^2+3k^2-7k^2= | | -4+5y=-34 | | 3.2(2x+2.1)-0.8=-1 | | y^3+2y^2=36y+32 | | 6b+6=8 | | 15=y-23 | | 6+4X+6X=126 | | -(c+d)-4d+5c-d=0 | | 3b+12+8=-3 | | (3a+b)(2a+b)= | | 2c+3c=109225 | | 2x+3y+4x+5y=0 | | 19g-4h+4-20(g-1)=0 | | x-.7=9.09 | | n+2n+4= | | 7y-27=-32+2y | | 9(k-4)=12 | | 58=-y+179 | | -11x+4+8x-4+3x=0 | | -3x-21=-81 | | -11x+4+8x-4+3x=o | | 5g+7g-4= | | 35x-7y=491 | | 2x+54=2(x+28) | | 4(2x+3)+8=2(X+3)+4 | | -2x-22=-54 | | x+x=270 |